PENDEKATAN ISLAMIC COGNITIVE BEHAVIORAL THERAPY (ICBT) DALAM INTERVENSI KLINIS UNTUK MENGATASI KENAKALAN REMAJA - Elfia Desi; Vivik Shofiah; Khairunnas Rajab (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Juvenile delinquency is a social problem that requires effective intervention. Islamic Cognitive Behavioral Therapy (ICBT) offers an alternative approach by combining cognitive-behavioral therapy and Islamic values based on the Qur'an and Hadith. This study aims to explore the application of ICBT in dealing with juvenile delinquency. The method used is library research by reviewing literature related to ICBT, cognitive-behavioral theory, and Islamic psychology. The results of the study show that ICBT is effective in helping adolescents change negative mindsets and deviant behavior, while strengthening spiritual values. This approach is considered relevant to the cultural and religious context of Indonesian society, and has the potential to strengthen adolescent character through the integration of psychotherapy and religious teachings.